Protection against herbivory in the mutualism between Pseudomyrmex dendroicus (Formicidae) and Triplaris americana (Polygonaceae) (2015)
Herbivory significantly impacts the growth and reproduction of plants. Many plants have developed ways to defend against herbivores and one common strategy is to associate with ants. In many ant-plant interactions, ants are known to protect their host. However, in the Neotropical ant-plant genus Triplaris, the benefits provided by associated ants have never been tested. Many Pseudomyrmex spp. ants are obligate inhabitants of Triplaris spp. trees. In this study, Triplaris americana was studied in association with Pseudomyrmex dendroicus, an ant highly specific to its host (it has not been collected from any other species of Triplaris). Ant exclusion experiments were carried out to assess the protective effect of ants. In addition, ant behavior was monitored in control plants to study the mechanisms by which ants might confer protection against herbivory. Ant removal led to a more than 15-fold increase in herbivory. Pseudomyrmex dendroicus are active at all times of day and night and aggressively and efficiently remove insect herbivores from their host. © 2016 Sanchez Adriana et al.